2003
DOI: 10.1046/j.1440-1614.2003.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Quality of Web Based Information on the Treatment of Schizophrenia and Attention Deficit Hyperactivity Disorder

Abstract: The Internet contains misleading information on both schizophrenia and ADHD. The methodology used in this paper could be adapted for other psychiatric conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
5
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 20 publications
6
82
5
6
Order By: Relevance
“…Overall, the majority of floaters/light flashes information on the Internet was of poor or fair quality (69.4%). Similar results have been reported for websites addressing other diseases (2,7,(12)(13)(14)(15)(16) .…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the majority of floaters/light flashes information on the Internet was of poor or fair quality (69.4%). Similar results have been reported for websites addressing other diseases (2,7,(12)(13)(14)(15)(16) .…”
Section: Discussionsupporting
confidence: 87%
“…16,17,20,22 All statements presented as fact were identified and collected. Statements that cited RFs or PSs that had been identified as having sufficient evidence for association with youth suicide by the reviews or that cited a variable as having no association that had been identified as such by the reviews were classified as SSEs.…”
Section: Website Assessmentmentioning
confidence: 99%
“…D'autres études ont utilisé un modèle similaire en combinant par exemple un « score de qualité de contenu » et le score de « DISCERN » (Griffiths et Christensen, 2002), trouvant ainsi une corrélation significativement élevée entre les deux scores. Dans le même sens, d'autres auteurs ont utilisé la présence du logo HON et les critères de Silberg (Hardwick et Mackenzie, 2003) ou d'esthétique (Kisely et al, 2003) mais n'ont pas nécessairement trouvé de corrélation avec la qualité de contenu dans les domaines étudiés.…”
Section: Grille D'évaluation Des Sitesunclassified
“…La grille de cotation a intégré les indicateurs suivants (annexe 1) : Les critères de Silberg et al (1997) ; Kisely et al (2003) ; Charnock et Shepperd (2004), permettent de mesurer « un score d'éthique » en 9 points. Ces critères s'intéressent aux questions suivantes : l'identité de l'auteur, son affiliation, ses références, ses sources d'information et leurs références, le promoteur du site, les sponsors sont ils dévoilés, ainsi que les dates de mise en ligne et de mise à jour du contenu.…”
Section: Grille D'évaluation Des Sitesunclassified
See 1 more Smart Citation